Kapabilitas Pemerintah Desa Dalam Pengelolaan Alokasi Dana Desa Di Desa Lanjut Kecamatan Singkep Pesisir Kabupaten Lingga - Muhammad Ronny Zulian; Jamhur Poti; Okparizan Okparizan (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2024)
The problem in the capability of the village government is that the village fund allocation has not been used for the reporting and accountability process. This research uses theories from Leonard-Barton (1992:4-5). This research uses a qualitative approach with a descriptive type of approach. The data collection techniques used are observation, interviews and documentation. Research results (1) In the indicators of knowledge and skills capability, the Advanced village government already has knowledge and skills, by implementing several actions in the process of managing village fund allocation. (2) In the technical system capability, the village government has been able to manage the allocation of village funds, due to its management techniques that are consistent with regent regulations and also regulations related to the allocation of village funds. (3) In the capability of the managerial system, the village government continues to manage the allocation of village funds, starting from planning to accountability, which has been transparent to the community by providing billboards and information boards regarding management information. (4) On capability values and norms, the village government continues to apply the values and norms obtained from training and education in managing the allocation of village funds and in providing services to the community. The conclusion of the study is that the capability of the village government in managing the allocation of village funds has not run optimally because there are still obstacles that have not been implemented digital systems or information technology in the process. The village government is expected to immediately apply information technology or digital systems in the process of managing the allocation of village funds to make it more transparent, accountable and accountable.